Carboxylated cellulose nanocrystal cryogel monoliths: a multi-tool study of morphology and porosity of pure and magnetite nanoparticle-decorated CNC scaffolds - Chen, Xining; Andrews, Mark P. (Frontiers in Soft Matter, 2023)
Porosity is an important tunable design parameter for bio-based scaffolds for tissue repair and regeneration. Scaffolds are known to benefit from incorporation of nanoscale bio-additives like cellulose nanocrystals (CNC). In this paper, we probe how a freeze-casting technique leads to a rescaling of specialty carboxylated cellulose nanocrystals (CNC) into macroscale cryogel scaffold monoliths. We adopt a multi-tool study of CNC scaffold structure and porosity. We examine porosity with scanning electron microscopy (SEM) coupled with Local Thickness Euclidean distance image processing, small-angle X-ray scattering (SAXS), and dynamic vapor sorption (DVS). Our findings address the importance of summoning different characterization tools to converge on a detailed picture of porosity in the CNC monoliths. We show that macropore morphologies of the cryogel scaffolds depend on the conditions under which ice formation takes place. Rapid freezing with liquid nitrogen, followed by lyophilization, yielded monoliths with lamellar and radially oriented small pores. Slow freezing at, following by freeze drying yielded scaffolds with large unoriented pores. A cycle of slow-freeze-thaw then rapid freeze (-12 o C freeze-thaw-rapid 77 o K freeze), followed by lyophilization yielded partially oriented scaffolds with 10-18 𝜇m pores. We studied the impact of a static magnetic field on the porosity and orientational anisotropy of pristine CNC and CNC monoliths decorated with magnetite nanoparticles. Magnetic field directed partial alignment is observed in -12 ℃ cooled samples, with or without Fe3O4 nanoparticles bound to the CNC surface. SAXS data fitted with a mass fractal model and power law suggest that the CNC particles aggregate to form welldefined compact walls in the range of 96.7 -27.3 nm for all samples, while inclusion of Fe3O4 nanoparticles disrupts this compactness in the range of 27.3 -4.8 nm. Analysis of DVS reveals that nanoparticles directly impact water uptake by the cryogel scaffolds and can reduce water sorption in mesopores with a radius of 5 -6 nm.